Epidemiology of human leptospirosis in Saint Lucia, 2010-2017 - Gemma Chery; Lorraine Francis; Shelly-Ann Hunte; Phil Leon (Pan American Health Organization, 2020)
Objective. To describe the epidemiology of human leptospirosis cases in Saint Lucia from 2010 to 2017 and determine whether there was a relationship between cases and rainfall and temperature. Methods. A retrospective analytical study was undertaken to describe the seasonal patterns of human leptospirosis cases reported to the Ministry of Health of Saint Lucia between 2010 and 2017. Confirmed cases of leptospirosis were analyzed according to age, sex, seasonality, and geographical distribution. Disease incidence was calculated and the association of cases with geographical distribution, rainfall, and temperature was investigated. Results. A total of 353 leptospirosis cases were reported between 2010 and 2017 and of these, 145 (40.6%) were laboratory confirmed. Cases were aged 7 to 73 years (mean 34 years; median 30 years) with a male to female ratio of 4.2:1. Six deaths were reported during the period, with an overall case fatality rate of 4.1%. There was no relationship between location (district) and incidence of leptospirosis in Saint Lucia. There was a weak correlation between rainfall and leptospirosis cases during the 8-year period (rs = 0.25, p = 0.015) but the correlation between cases and seasons was not statistically significant (dry season rs = 0.13, p = 0.42; wet season rs = 0.23, p = 0.08). There was no correlation between leptospirosis cases and temperature (rs = 0.07, p = 0.49). Conclusions. Leptospirosis has a seasonal distribution in Saint Lucia, with outbreaks during periods following increased rainfall and flooding, such as in the aftermath of tropical storms and hurricanes. Saint Lucia and other Caribbean countries should enhance surveillance for leptospirosis given the likelihood of increased flooding following frequent and intense rainfall due to climate change.